Interference Suppresion For UWB Receivers Using Adaptive Minimum BIT Error Rate Equalizer - Chin, Chung Gwo (2009)
In this thesis, our goal is suppress ISI and MAI in order to improve bit-error-rate (BER) performance of the UWB receivers. In the past, many receivers habe been proposed to overcome this problem.The most common approach used is the minimum mean square error (MMSE).